Potency Evaluation of Temulawak Through Physicochemical, Pharmacokinetics, Druglikeness, Water Solubility, Tox Prediction for KUB Chickens - Meireni Cahyowati; Dwi Ahmad Priyadi; Moh Hasbi Ash Shidiqi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Temulawak is one of the spices in Indonesia that is useful as a phytobiotic. Phytobiotics are beneficial for livestock in maintaining health, namely maintaining immunity, especially in chickens. One type of chicken that is widely cultivated in Indonesia is the KUB chicken to increase its productivity. This study aims to identify the potential compounds found in temulawak (Curcuma Xanthorrhiza). The research methods included literature studies and ADMET testing. The most abundant compound in temulawak was β-Curcumene with a molecular weight of 204.35 g/ml, a hydrogen bond donor count of 0, a hydrogen bond acceptor count of 0, and a TPSA value of 0.00 Å2 . The β-Curcumene compound is not classified as an inhibitor of CYP1A2, CYP2C19, CYP2D6, CYP3A4. β-Curcumene has drug-like properties according to the rules of Lipinski, Ghose, Veber, Egan but does not have drug-like properties according to Muegge's rules. The log S ESOL value of -4.93 is in the moderate solubility category, the log S SILICOS – IT value of -3.55 is good solubility, and the log S Ali value of -6.27 is in the poor solubility category. β-Curcumene has toxic compounds that are active and affect BBB-barrier performance by 97%, ecotoxicity target by 64%, estrogen hormone performance by 75%, and drug metabolism performance by 65%.